Revival and revivalism the making and marring of American Evangelicalism 1750-1858 - Murray, Iain H. 1931- (Edinburgh, Scotland Banner Of Truth Trust, 1994)
Includes bibliographical references and indexes.
Keywords: Evangelical revival -- United States -- church history, 1750-1858.